Post-General Anesthesia Angioedema After General Anesthesia - Mathilda Panggabean; Yutu Solihat (Solo Journal of Anesthesi, Pain and Critical Care (SOJA), 2022)
Background: General anesthesia includes the administration of avariety medicines to patient/in/ fairly short/period. Numerous negative consequences can occur because of reaction from the drugs given, one example is anaphylaxis that may lead to death if not been recognized and handled quickly & promptly.Case Illustration: A sixty-seven years old male patient 152 cm 65 kg with multiple cholecystitis and obstructive jaundice, who was scheduled to undergo laparoscopic cholecystectomy. Patient had no records of allergy to medication and food. Family has no records to hypersensitive reactions or angioedema. At initial evaluation, blood pressure was 190/90 mmHg and hemoglobin 10,4 g/dL while the rest parameter was within normal limits. We given propofol and rocuronium to induce relaxation and facilitate intubation in surgery. Approximately 90 minutes after rocuronium injection, patient evolved angioedema across the face/area, tongue, and floor of the mouth. Patient also complained of not being able to talk. Soon after that, we give 10 mg of dexamethasone and 100 mg hydrocortisone to the patient. Within 60 minutes after hydrocortisone administration the patient shows/clinical improvement that marked by swelling began to decrease and the patient was able to speak again. Then we educate patient about angioedema and its alert.Conclusion: Anaphylaxis is a type of hypersensitivity response that take place to a particular allergen and mostly self-limited, but 11% of hypersensitive reaction require airway intervention. Most of anesthetic medication such as thiopental sodium, propofol, muscle relaxants, and etomidate may induce anaphylactic reaction during anesthesia induction. Discontinuation of underlying agent and airway control may prevent mortality and morbidity.